Análise numérica da estabilidade lateral de vigas pré-moldadas de concreto com seção transversal assimétrica em içamento - Daura Neto, Ibrahim Abdallah (2020)
In the current scenario of civil construction, the search for cost reduction tends to optimize the processes and materials involved in the design, manufacture and maintenance of structural elements in reinforced and prestressed concrete. Therefore, elements with slender cross-sections and better mechanical performance arise, despite being more prone to the phenomenon of lateral instability during transitory phases, such as lifting. The main purpose of this work is to analyze, by means of numerical analysis in the computer program ANSYS, the behavior of precast beams with asymmetric cross section in the transient phase of lifting by cables, with respect to lateral stability, considering the influence of the variables regarding manufacturing and lifting processes. Parametric analyzes were performed to verify the effect of the variation of parameters on the lateral stability of beams, which are: girder length, position and angle of the cables, height of the lifting loops, characteristic resistance of the concrete, lateral sweep, lifting loops deflection, geometric properties of the beam’s cross section and prestressing force. The results show the relevance and the interference caused by each one of these parameters, of which the location of the lift points from the ends, the removal of the element that causes the asymmetry, and the lifting loops deflection stand out. The results also show the influence generated by the asymmetry in the cross section, whose existence considerably increases the equilibrium rotation angle of the cross section. For the analysis developed in this work, the removal of the elements that cause the asymmetry resulted in reductions in the equilibrium rotation angle between 30% and 50%. For the 45.57 m span beam, it resulted in about 20% reduction in the maximum tensile stress.